The age of Trump: the conscious consumer and social responsibility - paving the way forward - Steenkamp, Savannah (The IIE, 2017)
In the generation of the millennials, making a large consumer impact, there seems to be a peak of interest in the concern of social responsibility. In the context of a turbulent political situation in the United States, with controversial policies and ideologies that have shaken the world, brands and corporations. This study has examined the extent to which brands who have adopted a strong Corporate Social Responsibility are perceived or interpreted by mindful consumers in the political context of the newly elected United States President. Data was generated using interviews of ten people and 70 surveys. Through this interactive approach the study was able to illustrate the complexities and the subjective nature of the topic. The increased use of Corporate Social Responsibility voice of the brand adds to the brand identity, and growth whereas brands who have not acknowledged the turbulent times are viewed in a negative mindset of the conscious consumer and negative market share for a period of time however brand loyalty may still occur in some instances. Showing a casual loop between the voice of the brands as a response to the political context and the growth and perceptions of the consumers. Thus Corporate Social Responsibility can be used as a guideline for brands and consumers in the context of turbulent political environments.
Keywords: Corporate Social Responsibility; Consumer Behaviour; Politics; Political Economy; Brands; Branding